ARKEOLOGI FORENSIK: PERKEMBANGAN DAN CAPAIANNYA DI INDONESIA - Suriyanto, Rusyad Adi (BRIN, 2016)
Forensic archeology is defined as the application of archaeological principles and techniques in medico-legal and/or humanity context related to buried evidence. Forensic archaeologist has two roles, as the expert who unearth buried objects systematically and reconstruct them. This paper discusses the role of archeology and archaeologists in the excavation of criminal, humanitarian and disaster victims. Archaeologist’s role to reveal paleoanthropological materials smuggled and theft is also discussed in this paper. Humanitarian missions to investigate mass grave of victims of war, political strife and genocide in the past and the present are other archaeologist’s role discussed in this paper. The existence, condition and development of forensic archaeology in Indonesia emphasize the significance of new paradigm in Indonesian archaeology. Forensic archeology not merely focusess on the study of cultural materials of the past, education and museum development, cultural resource management and its advocacy, but it also has role in medico-legal works. Forensic archaeologist also engages in disaster victim identification (DVI) that addresses issues related to victims buried by either natural or human disasters.